2021
DOI: 10.1111/ajo.13297
|View full text |Cite
|
Sign up to set email alerts
|

HIPEC: Turning up the heat on ovarian cancer

Abstract: Clinical trials of heated intraperitoneal chemotherapy (HIPEC ) for the treatment of advanced ovarian cancer are showing promising survival outcomes. HIPEC has the potential to eliminate ovarian cancer cells from peritoneal surfaces more effectively than systemic chemotherapy through enhanced pharmacokinetic and hyperthermia effects. However, many questions remain to be answered, particularly regarding the true place of HIPEC in the current era of new and effective targeted treatments. Concerns around the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The OVHIPEC-2 study, an international multicenter RCT of HIPEC at the time of up-front surgery for stage III ovarian cancer was then started. The primary objective of the study was to evaluate the effect of HIPEC on the OS in patients with FIGO stage III epithelial ovarian cancers who were treated with primary cytoreductive surgery resulting in no residual disease, or residual disease up to a maximum dimension of 2.5 mm [ 18 , 32 , 33 ]. However, there were criticisms of OVHIPEC questioning the use of HIPEC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The OVHIPEC-2 study, an international multicenter RCT of HIPEC at the time of up-front surgery for stage III ovarian cancer was then started. The primary objective of the study was to evaluate the effect of HIPEC on the OS in patients with FIGO stage III epithelial ovarian cancers who were treated with primary cytoreductive surgery resulting in no residual disease, or residual disease up to a maximum dimension of 2.5 mm [ 18 , 32 , 33 ]. However, there were criticisms of OVHIPEC questioning the use of HIPEC.…”
Section: Resultsmentioning
confidence: 99%
“…The 3-year overall survival rate was 60.3% (95% CI: 55.3–65.0%) for patients undergoing primary cytorecductive surgery (PCS) plus HIPEC and 49.5% (95% CI: 41.0–57.4%) for patients undergoing PCS alone (weighted HR: 0.64; 95% CI: 0.50–0.82; p < 0.001). Complete PCS with HIPEC was associated with the best survival outcomes, with a median OS of 53.9 months and a 3-year OS rate of 65.9% [ 18 , 19 ].…”
Section: Therapeutic Effects Of Hipec In Epithelial Ovarian Cancersmentioning
confidence: 99%
“…What is important is that the administration of the drug takes place immediately after cytoreductive surgery. The advantage of HIPEC therapy is 10-20 times higher drug concentration delivered directly to cancer cells, compared to intravenous chemotherapy [109]. The results of multiple studies show that patients who received HIPEC therapy showed a significant increase in overall survival time, as well as an increase in progression-free survival [109].…”
Section: Combination Therapy With Cisplatin and Hyperthermiamentioning
confidence: 99%
“…A French multicenter randomized trial (CHIPOR; ClinicalTrials.gov identifier: NCT01376752) was initiated in 2011 and compares CRS alone with CRS plus HIPEC in patients with recurrent ovarian cancer. Interestingly, the recently initiated Australian HyNOVA (Hyperthermic versus Normothermic intraperitoneal chemotherapy following interval cytoreductive surgery for stage III epithelial OVArian cancer) will compare interval debulking and chemoperfusion with cisplatin (100 mg/m 2 , 90 min) at two different temperatures: 42.0 • C and 37.0 • C [72]. Currently, therefore, the available evidence supports the use of HIPEC in association with interval CRS in stage III EOC.…”
Section: Ovarian Cancermentioning
confidence: 99%